Examining Social Insurance Perceptions and Attitudes among Zimbabwean Informal Sector Workers: A Study on Providing Social Protection to the Disenfranchised - Mutanda, Bronson; Nomlala, Bomi Cyril (TIJAB (The International Journal of Applied Business), 2024)
Background: Given the rate at which the labour force in Zimbabwe's informal sector continues to evolve, steps need to be taken to promote a culture where employees contribute towards their social insurance. Social insurance is significant since it helps informal sector workers to prepare for life's predictable and unpredictable events, such as retirement, unemployment, old age, incapacity, death and health challenges.  Objective: Motivated by the increasing number of workers in the informal sector in Zimbabwe, this study aimed to explore the attitudes and perceptions of this group of people towards social insurance coverage and investigate strategies for extending social insurance to informal sector workers. Method: To achieve the objectives, convenience sampling was employed, and 115 questionnaires from informal sector workers of Jerera Growth Point were analyzed. Data collection involved the use of a questionnaire. A convergent parallel research design was adopted, with quantitative and qualitative data being analyzed to gain insight into the perception of informal sector workers. Results: The study's findings demonstrate that workers in the informal economy have a negative attitude towards social insurance coverage. Additionally, the results demonstrate that the age of informal sector workers affects their intention to contribute towards social insurance coverage. The results also demonstrate that employees in the informal sector need more basic knowledge about social insurance and how to apply for social insurance coverage. Conclusion: The study concluded that workers in the informal economy lack faith and confidence in those who provide social insurance services, explaining why they perceive social insurance coverage negatively.     Keywords: coverage, informal, insurance, pension, social, retirement